ULTRASOUND IN THE DETECTION OF MASTOPATHY IN WOMEN (Центральноазиатский журнал образования и инноваций, 2025)
Mastopathy is one of the most common benign breast diseases in women of reproductive age. According to the World Health Organization, more than 60% of women aged 20 to 48 years are affected by various forms of mastopathy. The disease is characterized by an increase in connective and glandular tissue, which can lead to the development of nodular formations and an increase in the risk of oncological processes. In this regard, timely diagnosis is of great importance, which allows detecting pathological changes in the early stages and preventing possible complications. Ultrasound (ultrasound) is a non-invasive, convenient and safe method for diagnosing breast diseases. Unlike mammography, ultrasound does not expose the patient to ionizing radiation, which makes it the preferred method for examining women under 40 years of age. In addition, ultrasound allows you to assess the structure of the mammary gland in real time, detect even minor changes, and monitor the dynamics of the condition during treatment. However, despite the widespread use of the method, questions remain about its sensitivity and specificity in diagnosing various forms of mastopathy.